Pembangunan Pertanian: Pemasungan Kebebasan Petani - Yunita Winarto; Maidi Darmowiyoto (Antropologi Indonesia, 1999)
Scientific knowledge is becoming the basis for action by policy makers and bureaucratic at the cost of other knowledge systems. In this article, the authors discuss this problem and raise the issue of the more fundamental problem of local communities losing the freedom to develop their own strategies for resource management. Their argument is based upon findings from the field of agriculture. Since the Green Revolution of the 1970's, farmers have been forced to plant specific varieties of rice and use specific fertilizer and pesticides. Farmers no longer experiment with other varieties of rice, leading to degradation in biodiversity and the farmers' own local knowledge system. The problem has been somewhat alleviated by the introduction of integrated pest management, which has allowed farmers to make discoveries through observation and discussion, and to make their own decision. However, food shortages in 1997-1998 have led the government to return to programs emphasizing high production targets through a planned, top-down model for agriculture.